2005
DOI: 10.1111/j.1365-2929.2005.02178.x
|View full text |Cite
|
Sign up to set email alerts
|

Just a spoonful of humanities makes the medicine go down: introducing literature into a family medicine clerkship

Abstract: BACKGROUND This project introduced medicinerelated poetry and prose to a Year 3 family medicine clerkship with the purpose of determining students' perception of the usefulness of such materials to enhance empathy, improve patient management, and reduce stress. Although humanities are represented in the curricula of many medical schools, we need more information on how best to incorporate them during the clinical years.METHOD In 2000, we used a needs assessment survey to identify learner perceptions of medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 14 publications
0
33
0
2
Order By: Relevance
“…34 A humanities-based curriculum consisting of readings linked to clinical vignettes, comments about humanities reading in required clinical Subjective, Objective, Assessment, Plan (SOAP) notes, and either station-specific or general poetry accompanying student end-of-clerkship objective structured clinical examinations was implemented in the teaching of family medicine curricular venues. 35 Learning from these experiences, we provide some implementation model of humanistic education for Chinese pharmacy undergraduates to find out suitable model for future humanistic education aiming at enhancement of empathy. The results showed that Chinese pharmacy undergraduates may have an affinity for implementing humanistic education in a vivid and free way, such as interesting social and extracurricular activity.…”
Section: Discussionmentioning
confidence: 99%
“…34 A humanities-based curriculum consisting of readings linked to clinical vignettes, comments about humanities reading in required clinical Subjective, Objective, Assessment, Plan (SOAP) notes, and either station-specific or general poetry accompanying student end-of-clerkship objective structured clinical examinations was implemented in the teaching of family medicine curricular venues. 35 Learning from these experiences, we provide some implementation model of humanistic education for Chinese pharmacy undergraduates to find out suitable model for future humanistic education aiming at enhancement of empathy. The results showed that Chinese pharmacy undergraduates may have an affinity for implementing humanistic education in a vivid and free way, such as interesting social and extracurricular activity.…”
Section: Discussionmentioning
confidence: 99%
“…Only ten articles included any formal method of evaluation or assessment of impact beyond learner satisfaction. Of those ten articles, five used qualitative techniques to evaluate learners (Thompson 2015, Ramani 2013, Gulpinar 2009, Wachtler 2006, Bonebakker 2003, three used quantitative measures (Rodriguez 2013, Wiecha 2008, Wiecha 2002, and two used a combination (Shapiro 2004, Shapiro 2005. Quantitative measures were typically Likert scales or validated empathy scales (Empathy Construct Rating Scale and the Balanced Emotional Empathy Scale (Shapiro 2004).…”
Section: Resultsmentioning
confidence: 99%
“…A few studies pointing to efficacy, indicate that medical humanities programs are beneficial for strengthening the students' empathy, deepening their understanding, enabling them to manage conflict, helping them to express themselves more efficiently, endowing them with a social and humanistic perspective, making them grasp life experiences related to medical practice and develop a new line of insight (Shapiro & Hunt 2003;Shapiro et al 2005;Lee & Ahn 2004). These programs also function as a tool to open discussions about 'biological determinism', 'technicalism' and 'proceduralism'.…”
Section: Discussionmentioning
confidence: 99%
“…The few articles on the subject conclude that these programs have positive effects on the students' patient management skills by enhancing empathy, improving understanding and reducing frustration. (Shapiro & Hunt 2003;Shapiro et al 2005). The aim of this article is to evaluate the HIM program of our faculty with regard to its efficacy and on the basis of the impressions of the students.…”
Section: Practice Pointsmentioning
confidence: 99%